Creep analysis of concrete columns by using finite element method - Tran, Kim-Bang; Nguyen, Quang-Sang; Truong, Tich-Thien (Vietnam Journal of Science and Technology, 2020)
The authors have carried out studies on long term behavior of concrete-filled steel tubular (CFST) column by numerical methods based on experimental data that is described by a visco-elastic model, and the age-adjusted effective modulus (AAEM) method is adopted to modeling creep behavior of the concrete core, which is evaluated by the Finite Element Method (FEM) combined Prony’s series interpolation by using ANSYS software. The CFST column with circular sections under long term sustained loading are performed, ensure the ultimate load bearing capacity of the members is limited to cause cracks. In the material modeling, the confining effect of the concrete was taken into account while the steel was modeled as a bilinear kinematic hardening model with perfect bond between concrete and steel. The scope of applicability, advantages over other methods and limitations are discussed in detail.